Pendampingan Anak Balita Dan Remaja Di Desa Balakka Padang Lawas Utara Melalui Kegiatan Kuliah Kerja Nyata - Raja Ritonga; Fuadi Fuadi; Anwar Husein; Nasution, Abdul Lohir Rosyid; Rizka Nailah Lubis; Ummi Amira; Ida Sumarni; Nur Hayati; Nur Fifiyani Nst; Nur Paridah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
Toddler and Adolescent ages are phases that have great potential in forming a child's character. Education and morality are the topics most often compared in discussions between toddlers and teenagers. Balakka Village in North Padang Lawas has children under five and teenagers whose daily education is not provided outside of school. Of course, this means that a lot of children's time is wasted. Even though this age is the right moment for the formation of their character. The service is aimed at providing assistance to all Balakka village communities in North Padang Lawas. The dedication method is carried out by delegating Community Service Students (KKN) starting from program planning, program implementation and program evaluation. The results of the service show that the people of Balakka village in Padang Lawas Utara, with their strong customs, can be open to input and changes given by KKN students. Character development and basic education provided by students through the magrib recitation program, courses, Islamic boarding schools, game education and other forms of assistance can provide new impressions and experiences for members of the public, especially children aged toddlers and adolescents.